Association between Periodontitis, Genetic Polymorphisms and Presence of Coronary Artery Disease in Southern Brazil - Rocha,Luiz Otavio (2020)
Abstract Background: Periodontitis and coronary artery disease (CAD) share an inflammatory etiology; there is a recent concern regarding the investigation of an association between these two conditions. Current theories indicate that cytokines and proteins have an important role in this process. C-reactive protein and interleukin-6 are inflammatory derivatives produced in the presence of periodontitis and in the pathophysiology of coronary disease. The polymorphisms of CRP + 1444 C > T and IL6-174 G > C are recognized in the literature as being related to CAD. Objective: This study investigates the association between periodontitis and coronary artery disease, through the presence of PCR and IL-6 polymorphisms. Methods: We selected 80 patients who underwent diagnostic catheterization in the HU of UFSM. The presence of periodontitis was determined by the Community Periodontal Index, whereas the CAD was established by the medical report. DNA was collected from a saliva sample and the presence of polymorphism was determined by PCR and restriction enzymes. A significance level of 5% was adopted. Results: The mean age of all participants (p = 0.035, OR 2.65; 95%CI: (1.02-6.87) male gender (p = 0.012, OR 3.37; 95% CI: (1.28- (p = 0.013, OR 3.66; 95% CI: (1.27-10.5)), PCR polymorphism + 1444C > T (p = 0.001, OR 6.37; 95% CI:, (2.25-17.9)) and IL6 -174 G > C polymorphism (p = 0.025, OR 2.87, 95% CI: (1.09-7.55)) were statistically associated with the presence of CAD. Age > 60 years and presence of the PCR +1444 C > T polymorphism remained independently associated with CAD after adjustment by logistic regression. Conclusions: The presence of the PCR + 1444 C > T polymorphism in this study was independently associated with the presence of coronary artery disease.